KAJIAN PENGGUNAAN DATA INDERAJA UNTUK PEMETAAN GARIS PANTAI (STUDI KASUS PANTAI UTARA JAKARTA) - Winarso, Gathot; Joko, Haris; Arifin, Samsul (Jurnal Penginderaan Jauh dan Pengolahan Data Citra Digital, 2009)
Shore line is important to define seawater administration borders of a province, a district, and a city related to decentralization. The shore line can be extracted from remote sensing data. However, the definition of vertical datum reference for the shore line and low water level place are totally different. The sea water level position for shore line used in the hydrographic mapping is mean high sea level (MHSL), while the sea water level for shore line used in the geodetic mapping is mean sea level (MSL). However, remote sensing data were recorded in specific time that also have a specific sea water level, might be in a high or a low sea level depending on the location. Objectives of this research are to understand the position of the sea water level for the shore line mapping when the Landsat 7 is acquired and how to adjust to make a standard shore line definition. The landsat ETM+ composing of 543 (RGB) Maritime and Navigation Map of 1 : 50.000 scale were overlaid and compared in same condition of spheroid, datum, and projection system. In the area where there is no significant change due to the dynamic of coastal processes, the result of the overlaid image and map indicated that the shore line matched between each other. However, in the area where there are some indicated change, resulted on some differences between the shore line from the image and the map. The sea level position when the image was acquired was in high sea level and the image shore line was as same as the hydrographic shore line. There are two conditions when an image is acquired on a difference water level position. The shore line position would not change in area without 0 meter contour line and would change in area have 0 meter contour line. Adjustment should be made in the second condition.